Analysis of Alternative Substitute Materials for Concrete Production Using Word Cloud - Andaryati Andaryati; Akbar Bayu Kresno Suharso; Danang Setiya Raharja; Nia Saurina (Universitas Muhammadiyah Purwokerto, 2026)
Concrete is a construction material whose use continues to increase every year. This need is based on concrete forming materials, especially cement, which has experienced quite a large increase. Word cloud is a system that creates visualizations of words by emphasizing the frequency of occurrence of related words in written discourse. This research uses the text mining method with the help of Word Cloud and Term Document Matrix to analyze 76 articles as a dataset that discuss various concrete substitute materials including husk ash, dry bamboo leaves, construction waste, husk ash, and shells. The use of Word Cloud in the analysis of concrete substitute materials provides a fast and effective visualization of the frequency and relevance of words in the text and helps identify environmentally friendly substitute materials, the most widely used in the industrial world and has concrete compressive strength according to concrete quality standards based on the frequency of word occurrences. key in the dataset